Optimalisasi Layanan Administrasi Kependudukan: Evaluasi Kualitas Pelayanan Pembuatan E-KTP di Dinas Kependudukan dan Catatan Sipil Kota Cimahi Tahun 2023 - Setiawan, Agustina; Agnessya, Alfira; Febriansyah Rokhmat, Dicky (Universitas Muhammadiyah Sorong, 2024)
The service for making e-KTP is not optimal yet in the implementation of services to the community. This was identified as being influenced by the public's lack of knowledge in processing documents, lack of human resources, and limited service time. The purpose of this article is to describe and analyze the quality of services from the Population and Civil Registry Service in making E-KTPs in Cimahi City in 2023. The research method uses descriptive with a qualitative approach. using the Hardiansyah (2011) service quality which is measured through several service quality indicators, namely: tangible aspects, level of reliability, ability to respond to guarantees, ability to empathize. Informants include 3 informants from the Cimahi City Population and Civil Registry Service staff and 3 informants representing the general public who use E-KTP. Data collection techniques through library studies and field studies (observation and interviews). Data Analysis Techniques through data reduction, data presentation, and drawing conclusions. The results of the research show that the quality of E-KTP making services in Cimahi City can be categorized as not yet meeting the quality because human resources are still lacking and network limitations are inadequate, time uncertainty for the community means that the quality of services provided to the community is not yet optimal.